CHATGPT AND VIRTUAL TEACHING ASSISTANTS: ENHANCING TEACHER-STUDENT INTERACTIONS IN THE DIGITAL CLASSROOM - Rustiyana Rustiyana; Park Jihoon; Charlotte Thomsen (Al-Hijr: Journal of Adulearn World, 2026)
The rapid adoption of digital technologies in education has prompted the exploration of innovative tools to enhance teacher-student interactions in virtual classrooms. Among these tools, AI-powered virtual teaching assistants, such as ChatGPT, have emerged as promising solutions to address challenges related to engagement, feedback, and personalized learning. However, despite their growing presence, the specific role of ChatGPT in improving interactions within digital classrooms remains underexplored. This study aims to investigate the impact of ChatGPT on teacher-student interactions, focusing on its ability to enhance engagement, provide personalized feedback, and support administrative tasks. A mixed-methods approach was employed, combining surveys, interviews, and usage logs from 30 teachers and 150 students across high school and university settings. The results indicate a significant improvement in engagement and feedback quality, with both teachers and students reporting increased satisfaction and interaction efficiency. Additionally, ChatGPT’s role in managing routine administrative tasks was found to alleviate teacher workload. The study concludes that ChatGPT can effectively complement traditional teaching methods by facilitating more interactive, personalized, and efficient learning experiences in digital classrooms. Future research should explore the long-term effects of AI tools on education and address ethical considerations such as data privacy and algorithmic bias.